2023
DOI: 10.1007/s00268-023-07092-4
|View full text |Cite
|
Sign up to set email alerts
|

A Neural Integrity Monitor Electromyography Endotracheal Tube Causes More Severe Postoperative Sore Throat Than a Standard Endotracheal Tube in Adults: A Prospective Cohort Study

Abstract: Background This study aimed at figuring out the different effects of a neural integrity monitor electromyography endotracheal tube (NIM-EMG-ETT) and a standard endotracheal tube (ETT) on postoperative sore throat (POST). Methods This prospective cohort study enrolled 143 patients scheduled to undergo general anesthesia with endotracheal intubation. Patients were allocated into three groups: Group A, non-thyroid surgery with a standard ETT; Group B, thyroid surgery with a standard ETT; Group C, thyroid surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…We read with great interest the recent article by Liu et al [1] comparing the influences of different endotracheal tubes on the occurrence of postoperative sore throat (POST) by a prospective cohort study in patients undergoing thyroidectomy. They showed that a neural integrity monitor electromyography endotracheal tube (NIM-EMG-ETT) resulted in a higher incidence of POST and a worse severity of POST than a standard endotracheal tube.…”
mentioning
confidence: 99%
“…We read with great interest the recent article by Liu et al [1] comparing the influences of different endotracheal tubes on the occurrence of postoperative sore throat (POST) by a prospective cohort study in patients undergoing thyroidectomy. They showed that a neural integrity monitor electromyography endotracheal tube (NIM-EMG-ETT) resulted in a higher incidence of POST and a worse severity of POST than a standard endotracheal tube.…”
mentioning
confidence: 99%